Antioxidant activity of extract from some squid species in Khanh Hoa - Anh, Nguyen Phuong; Ky, Pham Xuan; Ha, Dao Viet; Hy, Le Ho Khanh; Thiet, Doan Thi; Vy, Phan Bao (Vietnam Journal of Marine Science and Technology, 2021)
The antioxidant activities against DPPH free radical of crude extracts using ethyl acetate and methanol from ink sac, muscles, and bones of 5 squid species (Uroteuthis chinensis, Uroteuthis sibogae, Uroteuthis duvaucelii, Sepia esculenta, Sepioteuthis lessoniana) collected in Khanh Hoa waters were investigated. These activities ranged from 4.21% (ethyl acetate extract from ink of U. chinensis) to 54.51% (methanol extract from muscle of S. esculenta.). The functional group analysis by infrared adsorption spectrum (FTIR) in these crude extracts revealed the absorption peaks of melanin in ink, polysaccharide in bone and protein in muscle extracts. In addition, the SDS-PAGE result of some methanol extracts showed the presence of proteins with a molecular weight of 30-150 kDa.